THE ROLE OF THE LITERACY HOUSE "GUBUK BHAVANA" IN FOSTERING LITERACY CULTURE IN THE NGEPANREJO VILLAGE - Maria Indah Freshintia; Eny Ratnasari; Mutiara Sakuntala Kusuma; Yonanda Dwiqi Sabila Cahyani; Ananda Gadis Anggun Romadhona (As-Sidanah, 2024)
The literacy culture in Ngepanrejo Village still needs to be more profound. One effective way to raise awareness of the importance of literacy was creating a literacy house. This article aims to describe the role of the "Gubuk Bhavana" Literacy House in fostering a literacy culture in the Ngepanrejo Village community. This program used some methods, such as lectures, tutoring, problem-based learning, direct one-on-one communication, and focus group discussion. The role of the "Gubuk Bhavana" Literacy House in fostering a culture of literacy in the community is as follows: first, facilitate a reading place in the Literacy House located in Posong Hamlet and 5 Literacy Corners spread across the village as attractive as possible to create a comfortable atmosphere. Second, a collection of books tailored to the target readership was provided, such as those tailored to the work of the people of Ngepanrejo Village, from elementary and middle school students homemakers, and farmers. Third, conducted teaching to elementary school students and regular discussions with film screenings. Fourth, new skills training for homemakers was conducted. Fifth, the formation of an information-aware community. In the future, "Gubuk Bhavana" needs the involvement of religious figures to share the vision of this program so it could maximize the effectiveness of "Gubuk Bhavana" Literacy House.